2010
DOI: 10.1073/pnas.1005582107
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of DNAX accessory molecule-1 (DNAM-1) in the development of acute graft-versus-host disease in mice

Abstract: Acute graft-versus-host disease (GVHD) is a life-threatening complication following bone marrow transplantation; however, no effective molecular-targeting therapy has been determined. Here, we show that mice that received allogeneic splenocytes deficient in DNAX accessory molecule-1 (DNAM-1) had significantly milder GVHD and lower mortality than those that received allogeneic WT splenocytes. Donor CD8 + T cells deficient in DNAM-1 showed significantly less proliferation and infiltration of the liver and intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 40 publications
2
59
1
Order By: Relevance
“…Surprisingly, DNAM-1 had negligible impact on acute GVHD severity in this setting, regardless of the donor CD8 T-cell dose (2 3 10 6 or 0.1 3 10 6 T cells; Figure 2A). This is in contrast to the previous description of DNAM-1 expression on CD8 1 T cells exacerbating GVHD when very high numbers of donor T cells are transplanted (50 3 10 6 splenocytes or 12 3 10 6 T cells) after sublethal conditioning, 25 a system that may reflect GVHD after nonmyeloablative conditioning. We therefore analyzed the effect of DNAM-1 expression on donor CD4…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…Surprisingly, DNAM-1 had negligible impact on acute GVHD severity in this setting, regardless of the donor CD8 T-cell dose (2 3 10 6 or 0.1 3 10 6 T cells; Figure 2A). This is in contrast to the previous description of DNAM-1 expression on CD8 1 T cells exacerbating GVHD when very high numbers of donor T cells are transplanted (50 3 10 6 splenocytes or 12 3 10 6 T cells) after sublethal conditioning, 25 a system that may reflect GVHD after nonmyeloablative conditioning. We therefore analyzed the effect of DNAM-1 expression on donor CD4…”
Section: Resultscontrasting
confidence: 53%
“…In the sublethal conditioning system, we noted a trend to protection from GVHD in the absence of DNAM-1 that was also independent of T reg ( Figure 4B), in contrast to that seen after myeloablative conditioning ( Figure 4A). This is consistent with effects of DNAM-1 on other donor T-cell populations, particularly CD8 T cells, after sublethal conditioning, as described by Nabekura et al 25 To study whether functional differences may also exist in T reg in addition to the numerical effects seen in the absence of DNAM-1, adoptive transfer experiments were undertaken, as previously described, 26 Figure 5A) from B6.WT or B6.DNAM-1 2/2 mice. Two days later, 5 3 10 5 T reg -depleted WT T cells were transplanted to induce acute GVHD.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…We appreciate the comments of Seth et al (1), because they provide an important finding that is supplementary to our paper (2). They show that recipient mice deficient in CD155 (Cd155 −/− mice), a ligand for DNAM-1 (DNAX accessory molecule-1, CD226), exhibited shorter rather than longer survival than WT mice after bone marrow transplantation (BMT) with full MHC disparity.…”
mentioning
confidence: 93%
“…Recent studies have shown that the absence of CD226 promotes Treg proliferation and the suppressive function of Tregs in a murine graft-versus-host disease (GVHD) model [10,11]. Anti-CD226 treatment was shown to reduce the development of GVHD and alleviate the severity of developed GVHD, which is dependent on an increase in Foxp3 + CD4…”
Section: Introductionmentioning
confidence: 99%